Internal and external barriers to effective supply chain management implementation in Malaysian manufacturing companies: a priority list based on varying demographic perspectives - Anis, Azilah; Islam, Rafikul; Hashim, Hizam; Abdul Rahim, Abdul Rahman (Exceling Tech, UK, 2019)
Successful implementation of supply-chain management in a developing country such as Malaysia is considered a major challenge due to lack of awareness and unclear missions and goals. Focusing on this idea, this article compares the ranking of various demographic groups in relation to the internal and external barriers experienced by Malaysian manufacturing companies. The identified lists of internal and external barriers are prioritised using the Analytic Hierarchy Process (AHP). Ten respondents with wide ranging experience in SCM provided the necessary information in the prioritisation exercise. The ranking of the respondents from different races, age groups, education levels, employment types, work experience and designations suggests significant variations between these groups in the ranking of the internal and external barriers. The findings of this research provide important information to company managers who desire to implement SCM in a multi-cultural setting such as Malaysia. The onus is on these managers to be cautious in developing a strategic plan for its effective implementation and also in designing programs to overcome SCM obstacles.